Cyber threats and digital governance in Ukraine and the EU in 2022–2024 in the context of ensuring cyber resilience - Olha P. Kotovska; Myron D. Pacai; Taras V. Tchaikovsky (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. The work is devoted to identifying key trends in cyber threats, analyzing types of vulnerabilities, as well as determining responsible groups and sectors that suffer the greatest losses. Data from open sources, including international and Ukrainian agencies and organizations on information security, as well as indices and reports of leading organizations in the field of cybersecurity and digitalization, are processed. The negative impact of the full-scale invasion of the Russian Federation into Ukraine on the global level of cybercrime is shown and it is proposed to increase the level of cyber resilience through the development of digital services and overcoming digital gaps (disruptions).
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: cybersecurity; cyber incidents; global risks; economic sectors; digital services